Particularities of Cu and Zn Nanoparticles Formation in a Magnetic Field - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Khan V. A. Valery Alekseevich; Tichy M. Milan; Kapran A. Anna; Izhoykin D. A. Dmitriy; Lenskii V. N. Vladimir Nikolaevich; Gamov D. L. Denis Leonidovich (2019, 2019)
Title screen